FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KELUHAN NYERI PUNGGUNG BAWAH PADA SOPIR BUS ANTAR KOTA ANTAR PROPINSI PO. NUSANTARA TRAYEK KUDUS – JAKARTA - Fikri Fahmi Amrulloh; Siswi Jayanti; Ida Wahyuni; Baju Widjasena (Jurnal Kesehatan Masyarakat (Undip), 2017)
The bus driver is a profession vulnerable against LBP because while driving work is done in sitting position with very long time (11-14 hours). Early survey obtained bus driver who had LBP was suspected due to several factors. This study interested in conducting research on factors (age, years of service, exercise habits, BMI and vibration) related with LBP. Study design used explanatory research with cross sectional approach. The population in this study there were 66 bus drivers. Sampling technique used purposive sampling counted 33 drivers who worked from Jakarta - Kudus. Research instrument used was Visual Analogue Scale (measuring LBP), vibration meter (vibration), scales and microtoise (BMI), and questionnaires (years of service and exercise habits). This study used statistical test rank spearman. Results represented 15 drivers suffered NPB and 9 drivers suffered moderate pain. Majority of driver’s age are adult category (36-45 years) and early elderly (46-55 years). 17 drivers have long years of service (> 25 years), 20 drivers have poor exercise habits, 24 drivers have fat BMI, 5 buses have risk vibration. Statistical analysis showed that there is relationship between exercise habits (p = 0.005) and vibration (p = 0.000) with LBP. Based on rank spearman test, there were significant relationship between exercise habits (p=0.005) and vibration  (p=0.000) with LBP. Meanwhile, there isn’t relationship between age, years of service, and BMI with LBP (p>0.05).The researcher recommend PO. Nusantara management to create training program and regular exercise program to the bus driver, and perform periodic maintenance of bus engines.